(untitled) (European Journal of Government and Economics, 2026)
This paper employs a new open economy macroeconomic model that incorporates cross-border worker migration to analyze the effects of government spending shocks. In this paper, we demonstrate that when the elasticity of substitution between products produced within the same country is close to 1, a relative increase in government spending in the home country reduces the relative level of consumption at home, depreciates the home currency, and leads to worker migration from the home country to the foreign country. The model demonstrates that as international worker mobility rises, the effect of a government expenditure shock on the relative home consumption diminishes, while the impact on the exchange rate intensifies. Moreover, the model demonstrates that an increase in government spending in the home country invariably leads to a deterioration in global welfare.